John Bunyan and Socinianism - Seager, Nicholas ca. 20./21. Jh. (The journal of ecclesiastical history, 2014)
This article recovers John Bunyan's engagement with Socinianism in his doctrinal and imaginative writings. After surveying the rise of Socinianism in seventeenth-century England, the article augments the known theological contexts of Bunyan's disputes with the Quakers and the Latitudinarians by showing that he charges these groups with slighting the Son and so associates them with anti-Trinitarian heresy. Bunyan's recourse when affirming the Trinity is to biblical typology, a hermeneutical method and manner of structuring narratives which Bunyan uses to uphold the embattled orthodox views of Christ's divinity, the propitiatory atonement and justification by faith.